Imposition of Maximum Sentences on Juvenile Offenders for Concurrent Offenses of Premeditated Murder and Theft - Puan Dinaphia Yunan; Tubagus Heru Dharma Wijaya; Ratu Lingga Sangkan Buana (Journal of Progressive Law and Legal Studies, 2026)
The global juvenile justice framework increasingly prioritizes restorative justice, imposing strict statutory sentencing caps predicated on diminished adolescent culpability. However, the rigid application of these mandatory leniency provisions to exceptionally heinous, multi-layered juvenile crimes precipitates a profound doctrinal collision. Utilizing a doctrinal legal methodology that integrates case and statute approaches, this article critically examines the tension between formal statutory limits and the pursuit of substantive justice in the Global South. By analyzing a landmark Indonesian judicial decision (Decision No. 3/Pid.Sus-Anak/2024/PN.Pnj) involving extreme concursus realis—premeditated mass murder, aggravated theft, and post-mortem sexual assault. This study demonstrates the critical inadequacy of inflexible juvenile sentencing caps. The findings indicate that strict adherence to the statutory maximum creates a severe proportionality deficit, effectively granting legal impunity for concurrent offenses and eroding public trust. Consequently, judicial officers in transitional democracies are functionally compelled to engage in judicial activism. Grounded in Sociological Jurisprudence and Progressive Law, the court's deliberate circumvention of positive law operates not as a subversion of authority but as a necessary mechanism of social engineering to prevent extrajudicial vigilante violence, restore moral equilibrium, and preserve the rule of law. Ultimately, this study contributes to the global jurisprudential discourse by proposing a critical theoretical framework that reconciles statutory leniency with substantive justice, offering actionable insights for future legislative reform and guiding judicial discretion in cases of extreme juvenile concursus realis.